Crafting the Perfect Cup: How Sustainable Barista Training Shapes Product Quality at Kedai Kosim, Indonesia - Gautama Sastra Waskita; Denny Rakhmad Widi Ashari (SINDA: Comprehensive Journal of Islamic Social Studies, 2025)
Sustainable service delivery has become increasingly critical for small coffee enterprises, yet the role of sustainability-oriented training in shaping product quality remains empirically underexplored. This study examines how Sustainable Barista Training influences beverage quality, operational performance, and sustainability behavior at Kedai Kosim, Indonesia. Using a qualitative case study design, data were collected through in-depth interviews, non-participant observations, and document review to capture the integration of sustainability principles into barista competencies and daily workflows. The findings reveal that sustainability-focused training enhances technical consistency, strengthens environmental awareness, and cultivates mindful resource use in coffee preparation processes. These improvements elevate key dimensions of service quality, including reliability, assurance, and responsiveness, while embedding sustainable practices into routine operations. The study contributes to the service management and sustainable hospitality literature by positioning sustainability competencies as a critical yet underrecognized driver of product quality in micro-scale coffee businesses. Practical implications highlight the importance of structured, experiential training to improve beverage consistency, reduce operational waste, and support SDG-oriented coffee shop management. Future research should explore multi-case comparisons and longitudinal assessments to evaluate the durability and scalability of sustainability-driven training models